The rise of bioinspired ionotronics - Wan, Changjin (2020)
Ionotronics is a concept which provides powerful tools and methods for narrowing the gap between conventional electronics and biological systems. Translational implementation of ionotronics gives birth to a wide range of novel and exciting paradigm breakers, which greatly innovates the development of the bio–technology interface. Herein, new trends and features of bioinspired ionotronics are presented, first introducing the basic mechanisms of ionotronic modulation and the essential building blocks. Despite its infancy, bioinspired ionotronics exhibit an unprecedented potential to advance a broad spectrum of applications such as robotics, neuromorphic engineering, and biosensing and readouts. Challenges and perspectives for the full exploitation of this concept for practical applications are also addressed. Leveraging bioinspired ionotronics shapes the interaction between human and machines in the future.